A Primer on Artificial Intelligence for Healthcare Administrators - Senthujan Senkaiahliyan, Jeremy Petch, Nigar Sekercioglu and Abi Sriharan (Healthcare Quarterly, 2024)
Healthcare administrators steer their organizations' strategic direction with an emphasis on quality, value and efficiency, aiming to improve patient outcomes and ensure operational sustainability. Artificial intelligence (AI) has become a transformative force in healthcare in the past decade, with Canadian health systems and research institutions investing in AI solutions to address critical healthcare challenges. This primer delivers a fundamental guide to essential AI concepts in healthcare and provides practical guidance to prepare organizations for AI readiness.
Keywords: artificial intelligence, AI, healthcare delivery, healthcare administrators, applications of AI, AI development, patient care